(untitled) (Research, Society and Development, 2022)
The following work aimed to analyze the effect of Efficient Microorganisms (EM) on the bioremediation of water contaminated by animal waste as well as the physical-chemical and microbiological parameters of the fermented EM and contaminated water. The EM was captured and activated using the homemade method. The protocol for collecting contaminated water and EM samples was in accordance with Standard Methods for the Examination of Water and Wastewater. Total and thermotolerant coliforms of both water and EM were investigated, using the most probable number (MPN) technique, known as the multiple tube method. The physical-chemical parameters (pH, total solids, sodium, nitrite, nitrate, chlorides, total hardness, apparent color, conductivity, and turbidity) of the contaminated water and the EM were evaluated. To assess the bioremediation potential of EM, 10 tests were performed with different percentages of dilution of microorganisms, which followed the following concentrations: 0.3; 1.0; 3.0; 20; 25; 30; 35; 40; 45 and 50% of EM. It was possible to verify that the physical-chemical parameters analyzed meet the prerequisites of the Ministry of Health with regard to water quality, however, regarding microbiological parameters, 99% of the samples proved to be unfit for human consumption. The fermentation of efficient microorganisms is free of the coliform group. As for bioremediation using EM low concentrations of 0.3 to 3 did not remedy the coliform group, however it was found that gradual concentrations of at least 25% of EM can remedy up to 78% of the coliform group